Sosialisasi Cara Membuat Desain Kemasan Produk Mockups dan Smartmockups pada Canva bagi Pelaku UMKM Desa Cikancung - Rohmanto, Ricky; Hadiansyah, Rian (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2023)
This activity aims to provide guidance to Micro, Small and Medium Enterprises (MSMEs) in Cikancung Village on how to make product packaging designs (packaging) mockups and smartmockups using the Canva platform. The method used in this activity is the Participatory Action Research (PAR) method.  In this context, PAR will involve MSME actors in Cikancung Village in the entire research process. The results of the activity show that MSME players in Cikancung Village can make product packaging designs mockups and smartmockups in Canva, including improving the quality of packaging design, improving product image and branding, facilitating promotion and marketing, attracting more consumers, increasing product competitiveness, saving production costs, increasing sales and profits.